2023
DOI: 10.1590/2175-8239-jbn-2022-0101en
|View full text |Cite
|
Sign up to set email alerts
|

Calcium carbide-ripened plantain induced alterations in plasma electrolytes concentration and kidney function in rats

Abstract: Introduction: Artificial fruit ripening agents such as ethanol, ethylene, ethephon, and calcium carbide (CaC2) is usually employed in stimulating the fruit ripening process. Currently, there is a paucity of information regarding the effects of various artificial fruits ripening methods on the health status of consumers. In this study, the physiological effects and possible health hazards associated with the consumption of plantain ripened by CaC2 and other non-chemical methods on the kidneys were investigated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(21 reference statements)
0
1
0
1
Order By: Relevance
“…Em artigo publicado no Brazilian Journal of Nephrology 5 , pesquisadores da Universidade de Benin, Nigéria, observaram que ratas alimentadas com bananas (Musa paradisíaca) artificialmente amadurecidas com CaC 2 apresentavam alterações eletrolíticas e renais. Ratas alimentadas com bananas amadurecidas naturalmente não apresen taram tais alterações.…”
Section: Substância Usada No Amadurecimento De Frutas Pode Causar Les...unclassified
“…Em artigo publicado no Brazilian Journal of Nephrology 5 , pesquisadores da Universidade de Benin, Nigéria, observaram que ratas alimentadas com bananas (Musa paradisíaca) artificialmente amadurecidas com CaC 2 apresentavam alterações eletrolíticas e renais. Ratas alimentadas com bananas amadurecidas naturalmente não apresen taram tais alterações.…”
Section: Substância Usada No Amadurecimento De Frutas Pode Causar Les...unclassified
“…In an article published in the Brazilian Journal of Nephrology 5 , researchers from the University of Benin, Nigeria, reported that female rats fed bananas ( Musa paradisíaca ) artificially ripened with CaC 2 showed electrolyte and renal alterations. Rats fed naturally ripened bananas showed no such changes.…”
mentioning
confidence: 99%